2015
DOI: 10.2147/opth.s93213
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the disc damage likelihood scale objectively measured by a non-mydriatic fundus camera in preperimetric glaucoma

Abstract: PurposeTo assess the correlation between the disc damage likelihood scale (DDLS) objectively measured by a non-mydriatic fundus camera, Heidelberg Retina Tomograph 3, and optic coherence tomography in preperimetric glaucoma.MethodsOne-hundred-twenty-five patients with preperimetric primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma (n=30) were included (mean age 58.9±15.9 years). All three devices graded the optic disc topography: Diagnosis 1 was defined as “outside normal limits”, while Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another method to evaluate the ONH is the DDLS, which was formerly measured by using a slit-lamp and can now be objectively analyzed by the Kowa fundus camera. The DDLS is a useful parameter in the diagnosis of preperimetric and advanced glaucoma and it showed a close correlation with visual field, CDR, and OCT parameters (23-26). This study presents the first objectively measured DDLS in uveitic glaucoma.…”
Section: Discussionmentioning
confidence: 84%
“…Another method to evaluate the ONH is the DDLS, which was formerly measured by using a slit-lamp and can now be objectively analyzed by the Kowa fundus camera. The DDLS is a useful parameter in the diagnosis of preperimetric and advanced glaucoma and it showed a close correlation with visual field, CDR, and OCT parameters (23-26). This study presents the first objectively measured DDLS in uveitic glaucoma.…”
Section: Discussionmentioning
confidence: 84%
“…A related study by Pahlitzsch et al . on patients with preperimetric primary open-angle glaucoma reinforced the predictive power of the DDLS, which makes it an important tool in diagnosing glaucoma 21 . Kara-José et al .…”
Section: Introductionmentioning
confidence: 80%
“…40 A significant correlation between DDLS and HRT-GPA has also been reported in pre-perimetric glaucoma, reinforcing its utility in the early stages of disease. 41 Kumar et al described a novel automated fundus image processing technique for glaucoma pre-screening comparing cup-to-disc and rim-to-disc ratio and reported greater sensitivity (0.97 vs 0.92), specificity (0.97 vs 0.91), and accuracy (0.97 vs 0.91) of rim-disc based assessment compared to cup-to-disc-based assessment. 42 Ichhpujani et al reported that a relative afferent pupillary defect (RAPD) was detected with a sensitivity of 84% when the difference in DDLS scores between the two eyes is greater than 2 using standard swinging flashlight test.…”
mentioning
confidence: 99%